Filler and Water Reducer Effects on Sedimentation, Bleeding and Zeta-Potential of Cement Paste - Peng Ya; Pedersen Bård; Ng Serina; de Weerdt Klaartje; Jacobsen Stefan (Nordic Concrete Research, 2018)
Bleeding and sedimentation quantify the stability of fresh cement paste, whereas the addition of fillers and water reducers affect the stability. The effect of various types of fillers and water reducers was investigated by measuring bleeding, hydrostatic pressure and electroacoustic zeta-potential. Depending on their characteristics and use, fillers can improve stability by reducing sedimentation rate and bleeding. The combined effects of fillers and water reducers on the sedimentation rates, quantified as time-dependent hydrostatic pressure changes (dp/dt) in fresh matrix, correspond to their effects on zeta-potentials. The influence of the water reducers on sedimentation and bleeding exceed that of filler type.